2013
DOI: 10.1016/j.exer.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imposed defocus of opposite sign on temporal gene expression patterns of BMP4 and BMP7 in chick RPE

Abstract: This study investigated the effects of imposed optical defocus on the expression patterns of bone morphogenetic protein 4 and 7 (BMP4, BMP7) in chick retinal pigment epithelium (RPE), as indicators of roles in postnatal eye growth regulation. BMP4 and BMP7 gene and protein expression patterns were characterized for retina, RPE and choroid tissues of young normal White-Leghorn chickens. The effects of short-term (2 and 48 h) exposure to monocular +10 and −10 diopter (D) lenses on RPE gene expression of BMP4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 58 publications
3
41
1
Order By: Relevance
“…33 Finally, recent studies have demonstrated differential expression of a number of genes in the RPE of eyes undergoing experimental manipulations perturbing normal eye growth. 34,35 …”
Section: The Role Of the Rpe In Eye Growth Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Finally, recent studies have demonstrated differential expression of a number of genes in the RPE of eyes undergoing experimental manipulations perturbing normal eye growth. 34,35 …”
Section: The Role Of the Rpe In Eye Growth Regulationmentioning
confidence: 99%
“…So far, there has been only limited study of the roles of RPE-derived growth factors and cytokines in postnatal eye growth regulation, 34,35 and results were not always conclusive due to the approaches used. For example, the combined tissue collection of the RPE and retina in early gene expression studies involving the chick precludes conclusion about the site of observed changes in expression.…”
Section: The Role Of the Rpe In Eye Growth Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically in young chicks, all show sign-dependent differential gene expression in RPE in response to short term, imposed optical defocus (2 or 48 h). 14, 15 Differential gene expression of BMPs has also been reported in combined retina/RPE samples in another study using the form-deprivation myopia chick model. 18 These results together open the possibility that the RPE acts as a conduit for relaying growth modulatory retinal signals to the choroid and/or sclera.…”
Section: Introductionmentioning
confidence: 86%
“…14, 15 In brief, for both eyes of each bird, refractive errors (RE) were measured using retinoscopy and axial ocular dimensions measured using high-frequency A-scan ultrasonography, both at the beginning and end of the lens treatment period. All measurements were performed under isoflurane anesthesia (1% in oxygen).…”
Section: Methodsmentioning
confidence: 99%